Ecoturism and cultural tourism: positive and negative impacts in the department of Boyacá, Colombia - Cruz Rodríguez, Nini Johanna (2021)
Various approaches are presented on tourism, ecotourism, cultural tourism and their positive and negative impacts in the department of Boyacá, Colombia; a region recognized for its environmental abundance and historical memory. By analyzing and systematizing the results of the research carried out during the last three years, the socio-cultural and economic environmental effects generated by ecotourism activities are described. The research is qualitative, of a descriptive level and bibliographic method. Necessary factors are highlighted as a starting point for the development of tourism activity that allows the enjoyment of current generations, without detriment to future generations.